2020
DOI: 10.1007/s00705-020-04790-5
|View full text |Cite
|
Sign up to set email alerts
|

Newly detected mutations in the Meq oncogene and molecular pathotyping of very virulent Marek’s disease herpesvirus in Tunisia

Abstract: Marek's disease (MD) is a contagious avian viral disease that is responsible for large economic losses to farmers. The disease is caused by Marek's disease virus (species Gallid alphaherpesvirus 2), which causes neurological lesions, immune suppression, and tumor proliferation of lymphoid cells that invade a large number of organs and tissues. Despite widespread vaccination, Marek's disease virus (MDV), has shown a continuous increase in its virulence and has acquired the ability to overcome immune responses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Although genetic analysis demonstrated the existence of high virulence MDV-1 strains in Taiwan, four unique substitution positions 119(R), 153(Q), 176(A) and 277(P) were not present when comparing with the classic vv+MDV strains N and 648A of USA. Moreover, as in previous reports, the proline content and the number of PPPP repeats within the Meq oncoprotein were also used as virulence predictors for Taiwanese strains [11,36]. Compared with vaccine and mild MDV-1 strains (Table 3), the Taiwanese strains lacked insertions and showed related lower proline contents as well as PPPP motif numbers, which supported the high virulence prediction.…”
Section: Plos Onesupporting
confidence: 74%
See 1 more Smart Citation
“…Although genetic analysis demonstrated the existence of high virulence MDV-1 strains in Taiwan, four unique substitution positions 119(R), 153(Q), 176(A) and 277(P) were not present when comparing with the classic vv+MDV strains N and 648A of USA. Moreover, as in previous reports, the proline content and the number of PPPP repeats within the Meq oncoprotein were also used as virulence predictors for Taiwanese strains [11,36]. Compared with vaccine and mild MDV-1 strains (Table 3), the Taiwanese strains lacked insertions and showed related lower proline contents as well as PPPP motif numbers, which supported the high virulence prediction.…”
Section: Plos Onesupporting
confidence: 74%
“…Although the causes for such high mutation frequency of MDV-1 have not been fully clarified, most investigations have demonstrated that the improper use of vaccines can lead to the induction of positive selection from the field viruses, eventually resulting in viral diversity [43,44]. With the annually found MD clinical cases and the genetic diversity of meq oncogenes in our results ( Specific sequence characterization of the Meq oncoprotein has been reported as a predictor for MDV-1 pathotype and can be applied to the virulence prediction for novel isolated MDV strains instead of in vivo classification [16,18,36]. It has been reported previously that amino acid mutations at positions 71 (Ala), 77 (Glu), 80 (Tyr), 115 (Ala), and 176 (Arg) were the main feature of highly virulent MDV-1 of Chinese strains [14,17].…”
Section: Plos Onementioning
confidence: 66%
“…All four strains had only the interruption of four consecutive prolines at position 217. Proline interruption at position 217 was reported by Lachheb et al (2020) when they analyzed Meq protein from Tunisian isolates (TN1013/16, TN1014/16). The interruption of four consecutive prolines was observed in all virulent strains except RB1B (Lachheb et al, 2020).…”
Section: Meq Gene Sequencingmentioning
confidence: 92%
“…Proline interruption at position 217 was reported by Lachheb et al (2020) when they analyzed Meq protein from Tunisian isolates (TN1013/16, TN1014/16). The interruption of four consecutive prolines was observed in all virulent strains except RB1B (Lachheb et al, 2020). In addition, Renz et al (2012) reported that v, vv, vv+ strains have been characterized by the presence of two to five repeats, and a low proline content has been shown to correlate with high virulence.…”
Section: Meq Gene Sequencingmentioning
confidence: 92%
“…Laboratory confirmation of MD was conducted using gross and histopathological diagnosis together with conventional polymerase chain reaction (PCR) techniques for detecting the meq gene on MDV. The presence of a meq gene indicated that the isolate had an oncogenic gene and was pathogenic [19][20][21].…”
Section: Outbreak Investigation and Estimation Of Economic Lossesmentioning
confidence: 99%